1978
DOI: 10.1038/ki.1978.154
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen balance during intermittent dialysis therapy of uremia

Abstract: Daily measurements of nitrogen balance were made at two levels of protein intake in five patients undergoing chronic intermittent dialysis therapy. During ingestion of high (1.4 g/kg of body wt) protein intake, nitrogen balance was positive on nondialysis days and negative on dialysis days, so that cumulative balance for the week of study was not different from zero. During ingestion of low (0.5 g/kg) protein intake, nitrogen balance was approximately zero on nondialysis days but was again negative on dialysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
125
0
3

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(131 citation statements)
references
References 21 publications
3
125
0
3
Order By: Relevance
“…These findings are consistent with the report of Borah et al (9), documenting that nitrogen balance is always less on the day of dialysis, and with our own data showing that lengthening the interdialytic interval tends to improve nitrogen balance (10). By measuring arterio-venous amino acid gradient and total blood flow across the leg, Gutierrez and colleagues ( 14) found that 150 min of sham hemodialysis in normal control subjects led to increased amino acid release, suggesting accelerated protein breakdown.…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…These findings are consistent with the report of Borah et al (9), documenting that nitrogen balance is always less on the day of dialysis, and with our own data showing that lengthening the interdialytic interval tends to improve nitrogen balance (10). By measuring arterio-venous amino acid gradient and total blood flow across the leg, Gutierrez and colleagues ( 14) found that 150 min of sham hemodialysis in normal control subjects led to increased amino acid release, suggesting accelerated protein breakdown.…”
Section: Methodssupporting
confidence: 81%
“…Furthermore, Farrell and colleagues (7) and Ward et al (8) noted that urea generation rate, calculated from urea ki-netics, is 30% higher during dialysis than during the interdialytic period. Using metabolic balance technique, Borah et al (9) noted that nitrogen balance is always less on the day of dialysis irrespective of the quantity of protein intake, and we have noted that dialysate nitrogen loss per day tends to be greater when the interdialytic interval is shorter ( 10). None of these studies, however, provide unequivocal evidence of dialysis-induced protein breakdown.…”
Section: Introductionmentioning
confidence: 53%
“…The seminal findings of Borah et al (5) that nitrogen balance is always more negative or less positive, depending on the intake, on dialysis days compared with nondialysis days greatly influenced the belief that HD is a protein catabolic procedure. Lim et al (6) also reported that nitrogen output, expressed as milligrams per minute, is greater when the interdialytic interval is 2 d as compared with 3 d, suggesting that each HD generates a certain degree of protein catabolism, the effect of which is minimized when the interdialytic interval is lengthened.…”
Section: Nitrogen Balance Combined With Urea Kineticsmentioning
confidence: 99%
“…Maintenance hemodialysis (HD) is a catabolic procedure that is associated with poor nutritional status (1,2). In addition to being catabolic, time spent undergoing treatment provides an added barrier to achieving adequate dietary intake and has been associated with significant reductions in nutrient consumption compared with nontreatment days (3,4).…”
Section: Introductionmentioning
confidence: 99%